Freire, P. y Shor I. (2014). Miedo y Osadía. La Cotidianidad del Docente que se Arriesga a Practicar una Pedagogía Transformadora - Germán Iván Martínez Gómez (Universidad Autónoma de Madrid, 2015)
ISBN: 9789876294096